Hydractinia angusta Hartlaub 1904 ... - Galea, Horia R.; Schories, Dirk (Zenodo, 2012)
Hydractinia angusta Hartlaub, 1904 (Pl. 1A–E, Fig. 2A–C) Hydractinia angusta Hartlaub, 1904: 7, pl. 4. — Naumov & Stepanjants, 1972: 35, fig. 1. — Stepanjants, 1979: 13, pl. 1 fig. 7. — Peña Cantero & Ramil, 2006: 950, fig. 2A. — Peña Cantero, 2012: 855. Hydronema angustum — Stechow, 1923: 67. — Totton, 1930: 138. — Briggs, 1939: 10. Hydractinia dendritica Hickson & Gravely, 1907: 9, pl. 2 figs 7–10. Hydronema dendriticum — Stechow, 1921: 252. — Stechow, 1923: 67, fig. F. ? Hydractinia sp. —Stepanjants, 1972: 59, fig. 4. Material examined. Stn. SHO — 16.ii.2011, Ant.09/2011 (43 m): fertile (female) colony on worm tube (MHNG- INVE-79798). Stn. ARD — 28.i.2011, Ant.11/2011 (39 m): fertile (female) colony on worm tube (MHNG-INVE- 79799). Description. Hydrorhiza an encrusting mat issued through the coalescence of the stolonal system, covered by naked coenosarc (Pl. 1C). Spines present, often continuous with each other (Pl. 1D), provided with low ridges of perisarc (Pl. 1E), open or closed at tips. ... : Published as part of Galea, Horia R. & Schories, Dirk, 2012, Some hydrozoans (Cnidaria) from King George Island, Antarctica, pp. 1-21 in Zootaxa 3321 on page 2, DOI: 10.5281/zenodo.213236 ...